Opinions on memorandum on help for Spain
1938-02-25 036-0013-002 PRIVATE OPINIONS ON MEMORANDUM ON HELP FOR SPAIN OF (1) The Counsellor to the Embassy, who writes "As the Ambassador's time is very fully occupied, I have signed it" (the following letter) "in his stead." Dear Sir, I am glad to hear that the Memorandum which you have drawn up for submission to the Labour Party Committee on help for Spain is being translated into Spanish, for I am sure that the Authorities in Spain will agree with me in regarding it as one of the most serious and important contributions that have been made. I should be glad if, immediately the translation is completed, you would be so good as to let me have about twenty copies which I shall send to my Government in Spain. I trust that your work will receive in England from the friends of Spanish Democracy the support which, in our opinion, it undoubtedly deserves. The analysis of the situation which you make is, I believe, correct. The suggestions you put forward are so important, and, if carried out in a thorough manner, capable of being of such real help, that it would add to their value if you would also work out suggestions for the methods of co-operation with the Spanish Authorities that would clearly be involved. Yours very truly, (Signed) ANTONIO de la CRUZ MARIN. (2) The former Chairman of the Spanish National Food Commission - Dear Mr. Pyke, I have very carefully examined your Memorandum to the Labour Party Committee on Spain and I am pleased to state that I am in complete agreement with its main points. My activities, during one year, as Chairman of the Spanish National Food Commission, enabled me to observe very closely the realities of the problems which, in your Memorandum, you expose so clearly and with such a profound knowledge of the matter. In this respect I am so fully identified with your exposition of the facts, that I should have no hesitation whatsoever in signing it as if it were mine. 292/946/36/13(ii)